Corporate social responsibility, industry competition and firm productive efficiency: evidence from semi-parametric and non-parametric analysis - Hamza, Taher; Nizar, Hamza; Lakhal, Faten (Annals of operations research, 2025)
This study examines whether corporate social responsibility (CSR) improves firm productive efficiency and highlights the role of product market competition in addressing agency conflicts associated with CSR. Using a sample of French firms from 2008 to 2018, we estimate firm productive efficiency through a semi-parametric and non-parametric methods (Data Envelopment Analysis—DEA). The results show that CSR positively affects firm productive efficiency supporting the instrumental stakeholder theory. We also find that the positive effect of CSR on firm productive efficiency is more prevalent among firms operating in highly competitive environments and standing out high governance quality. These findings suggest that agency problems related to CSR are less likely in firms subject to high external and internal control. These findings have several practical implications and may provide valuable insights in particular to the French National Productivity Council, which has been actively investigating the primary catalysts of firm productivity in France.